S’approcher des émotions d’autrui. Travail de terrain, éthique de care ? - Geoffrey Mollé; Chloé Morhain (GéoProximitéS)
This article reflects on the place of care in fieldwork in social sciences. Through two thesis in geography and planning, the authors have integrated the perspective of care into their fieldwork: through their approach to the emotions of local residents, or to the practices of vulnerable young people. In the context of academic research that is increasingly funded by private or institutional stakeholders, the instrumentalisation of proximity with surveys presents major ethical challenges.